Dinamika Kelompok Tani Hutan pada Pengelolaan Hutan Produksi Bersama Masyarakat di Perum Perhutani Unit I Provinsi Jawa Tengah - Suwignya Utama; Sumardjo Sumardjo; Djoko Susanto; Darwis S Gani (Jurnal Penyuluhan, 2010)
The collaboration on managing forest resource involves two main actors such as State ForestryCorporation (Perum Perhutani) and forest farmers groups. The objectives of this study are: (1) to explorethe conditions of factors that influence group dynamics of forest farmers group (FFG); (2) to explore thecondition of group dynamic of forest farmers group and to identify several factors influence the groupdynamic (3) to formulate a model of group dynamic of FFG. Several variables are included in this studysuch as potency of individual farmers, effectiveness of empowerment process, role of facilitators,effectiveness of forest farmers’ group leadershi, environmental supports and group dynamic of FFG. Thelocations of the study are in three forest districts area of East Pekalongan, South Kedu and Gundih. Thepreliminary study was carried out in January 2008, and field survey had been accomplished from July toAugust 2008. Populations of the study are forest villagers around state forest areas in three selectedlocations of 889.407 families. Method in this study is survey with questionnaire. Respondents of 408farmers were selected through multistage cluster sampling with disproportional number of respondentseach location. The research data were processed with descriptive analysis and structural equationmodeling (SEM) with LISREL 8.72. The conclusions of the study are: (1) The condition of effectiveness offorest farmers’ group leadership low (score 62); the condition of environmental support is low (score 62)and the condition of facilitators’ role is also low(score 62); (2) Level of group dynamic of forest farmers’group is low. Factors that influence significantly on the low of group dynamic are the low effectiveness offorest farmers’ group leadership, unfavorable environmental supports and low role of facilitators; (3)Model of effective group dynamic are influenced by effectiveness of forest farmers’ group leadership,favorable environmental supports and role of facilitators. Whereas group dynamic consists of goal of thegroup, group structure and group function.Keywords: Group Dynamic, Forest Villagers, Forest Farmers Group, Collaborative Forest Management, Social Forestry